Corporate Social Responsibility Activities in Small and Medium Enterprises and Their Contribution to Sustainable Development: A Study on Traditional Food Processing Industries in Indonesia - Faoziyah, Sitti; ., Candri; Putra, Dody Dahwana; ., Wahidin; Farah, Naila (Journal of Posthumanism, 2025)
This study explores the Corporate Social Responsibility (CSR) activities implemented by Small and Medium Enterprises (SMEs) in the traditional food processing industry in Cirebon, Indonesia. The research focuses on the impact of CSR on sustainable development, highlighting the ethical business practices and community involvement of SMEs producing traditional Indonesian foods such as tempe, wajik, kerupuk, and emping. Through observations and interviews, the study reveals that these SMEs prioritize the use of quality raw materials, maintain food safety standards, and recycle waste products for alternative uses. The businesses demonstrate significant contributions to the local economy by providing job opportunities and promoting local employment. Moreover, the research underscores the importance of legal compliance and consumer protection, particularly in ensuring product quality and hygiene. These SMEs also engage in eco-friendly practices, such as recycling and reducing waste, supporting a circular economy. This study emphasizes the role of CSR in promoting sustainable business operations and fostering positive social and environmental outcomes. In conclusion, the CSR practices of these traditional food SMEs serve as a model for other small businesses, contributing to both economic growth and environmental sustainability in rural areas. The findings suggest that continued support for CSR initiatives can further enhance the development of SMEs in Indonesia’s food industry.